Fables - Ross, Ronald, Sir, 1857-1932 (Salt Lake City, UT : Project Gutenberg, 2015)
"Fables" by Ronald Ross is a collection of poetic fables written during the late 19th century, specifically between 1880 and 1890 while the author was in India. This book features a series of allegorical tales that often explore themes of morality, truth, and human nature through whimsical characters and charming narratives. The content of "Fables" includes a variety of stories that present moral lessons through the interactions of anthropomorphized animals and mythical beings. Each fable is unique, such as "The Frog, the Fairy, and the Moon," which examines unrequited love, and "The Man, the Lion, and the Fly," which illustrates the futility of fighting great struggles while ignoring smaller irritations. Ross employs vivid imagery and lyrical language to create each tale, imbuing them with humor and wisdom, ultimately inviting readers to reflect on the human condition and ethical dilemmas inherent in life. Through fantastical elements and memorable characters, the book offers not only entertainment but also profound insights into virtues and vices. (This is an automatically generated summary.)
Release date is 2015-02-04
E-text prepared by David T. Jones, Mardi Desjardins, Neanderthal, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Humorous poetry